INVESTIGATING THE RELATIONSHIP BETWEEN STUDENTS’ SPEAKING CONFIDENCE AND FOREIGN LANGUAGE CLASSROOM ANXIETY IN INDONESIAN UNIVERSITY EFL SETTINGS - Riyadh Ahsanul Arifin; Eva Meidi Kulsum; Revi Nur Ridwan; Rina Mutiarawati (Universitas Duta Bangsa Surakarta, 2026)
This study examines the relationship between students’ speaking confidence and Foreign Language Classroom Anxiety (FLCA) among Indonesian university EFL learners. While previous studies have often investigated confidence and anxiety separately, limited research has explored their relationship at the tertiary level in the Indonesian context using a mixed-methods approach. To address this gap, the study employed a sequential explanatory mixed-methods design (QUAN ? qual). The participants were 24 English Education students selected through purposive sampling. Quantitative data were collected using a speaking confidence questionnaire and the Foreign Language Classroom Anxiety Scale (FLCAS), which demonstrated acceptable to excellent reliability (? = .704 for the FLCAS and ? = .933 for the confidence scale). Descriptive statistics and Pearson correlation analysis were conducted, followed by semi-structured interviews to confirm the questionnaire results. The findings showed that most students reported high speaking confidence while experiencing moderate classroom anxiety. Correlation analysis revealed a strong and significant negative relationship between confidence and anxiety (r = –0.657, p < .05), indicating that higher confidence was associated with lower anxiety levels. Interview data were consistent with the quantitative findings and confirmed students’ self-reported levels of confidence and anxiety. These results suggest that confidence and anxiety coexist in EFL speaking contexts rather than functioning as opposing states. Pedagogically, the study underscores the need for confidence-building speaking tasks and supportive classroom practices to help learners manage anxiety and sustain oral communication.